Examining the Factors Related to Mortality Aamongst One Year Old and Younger Children in Yazd City During 2011 to 2013 Period - Abbas Askari Nodoushan; Hossein Fallah zade; Hassan Fallah madvari (Shahid Sadoughi University of Medical Sciences, 2015)
Background: Provision, maintaining and improving health status of one year old and younger children as a vulnerable group has been considered as an important issue pertaining to healthcare/medical services. Index of mortality of under one year old children is among most important healthcare indices and is known as the most important index of healthcare status of any society as well as the quality of life in any region. The present study aims for examining causes of mortality amongst one year old and younger children who were covered by health centers in Yazd city during 2011 to 2013 period. Materials and Methods: This descriptive-analytical study was conducted using control-test group method. All recorded cases of mortality for children in Yazd city during the first year of their life were included in statistical population, while for each case of mortality two cases of living children were examined as control group. The data were collected by direct visits on healthcare centers in the city and examining case files for children. Obtained data were analyzed using SPSS 20 software package. Results: 116 mortality cases were examined in total which included 41.4% boys and 58.6% girls. Some variables such as type of marriage between parents, mother and father's education level, type of labor and number of previous pregnancies were significantly related to children's mortality rate. Conclusion: suggest that paying specific attention to infants at the time of birth, improving knowledge level amongst mothers and families, providing standard level healthcare prior to pregnancy and after that, and also developing programs which aim for improving economic-social and cultural status amongst women and men would be effective on reducing children mortality rates.